Increasing metabolic stability via the deuterium kinetic isotope effect: An example from a proline-amide-urea aminothiazole series of phosphatidylinositol-3 kinase alpha inhibitors. Issue 19 (1st October 2016) - Fairhurst, Robin A.; Caravatti, Giorgio; Guagnano, Vito; Aichholz, Reiner; Blanz, Joachim; Blasco, Francesca; Wipfli, Peter; Fritsch, Christine; Maira, Sauveur-Michel; Schnell, Christian; Seiler, Frank H.
Graphical abstract: Abstract: In vitro metabolic identification studies with a PI3K-α inhibitor lead molecule1 identified a single predominant site of oxidative metabolism to be occurring within a tert .butyl moiety. Modification of the tert .butyl group within the lead molecule1, to the corresponding d 9 - tert .butyl analogue2, led to an increase in both the in vitro and in vivo metabolic stability. This increase in metabolic stability resulted in a 2-fold increase in the oral bioavailability measured in the rat, and a 3-fold increase in potency in a chronic in vivo study in the mouse, for2 when compared to1 .